2003
DOI: 10.1038/sj.npp.1300365
|View full text |Cite
|
Sign up to set email alerts
|

Interdose Elevation in Plasma Cortisol During Chronic Treatment with Alprazolam but not Lorazepam in the Elderly

Abstract: Benzodiazepines (BZPs) have been shown to reduce hypothalamic-pituitary-adrenal (HPA) axis activity acutely in normal humans. In contrast, the effects of chronic BZP treatment on the HPA axis have not been well studied, especially in the geriatric population. This study examined the acute and chronic effects (3 weeks) of alprazolam and lorazepam on plasma cortisol in 68 subjects (60-83 years) who received 0.25 or 0.50 mg b.i.d. alprazolam, or 0.50 or 1.0 mg b.i.d. lorazepam, or placebo orally according to a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
(56 reference statements)
0
7
1
1
Order By: Relevance
“…These results are opposite from the results of a recently completed study (Pomara et al 2004), in which we found that chronic 21-day treatment with therapeutic doses of alprazolam (0.5 mg PO bid) in healthy elderly resulted in an increase in pre-drug morning plasma cortisol, which was related to increases in anxiety and depressive symptoms. The differential effects of chronic diazepam and alprazolam treatment on interdose cortisol levels suggest that intrinsic differences among BZPs in potency, elimination half-life, and other pharmacodynamic factors can impact on HPA axis activity and highlight the need for more prospective studies with multiple sampling times encompassing a 24-h period to confirm these findings.…”
Section: Discussioncontrasting
confidence: 84%
“…These results are opposite from the results of a recently completed study (Pomara et al 2004), in which we found that chronic 21-day treatment with therapeutic doses of alprazolam (0.5 mg PO bid) in healthy elderly resulted in an increase in pre-drug morning plasma cortisol, which was related to increases in anxiety and depressive symptoms. The differential effects of chronic diazepam and alprazolam treatment on interdose cortisol levels suggest that intrinsic differences among BZPs in potency, elimination half-life, and other pharmacodynamic factors can impact on HPA axis activity and highlight the need for more prospective studies with multiple sampling times encompassing a 24-h period to confirm these findings.…”
Section: Discussioncontrasting
confidence: 84%
“…Most studies on the effects of short-term BZD treatment (maximum of 3 months) on the hypothalamic-pituitary-adrenal (HPA) axis in human subjects reported a decrease in cortisol levels, 1Y11 although some studies reported mixed results. 12,13 These inconsistencies may be explained by differences in dosages and half-lives of the BZDs used 13 and by disparities in the time points used in the assessments (only predrug and postdrug measurements, 13 at certain time intervals, 6,8,10Y12,14 or for a full circadian cycle 1,2,5 ). Differences in patient groups, 12,13 and measurements of basal versus stress-provoked cortisol levels may also influence the results.…”
mentioning
confidence: 80%
“…12,13 These inconsistencies may be explained by differences in dosages and half-lives of the BZDs used 13 and by disparities in the time points used in the assessments (only predrug and postdrug measurements, 13 at certain time intervals, 6,8,10Y12,14 or for a full circadian cycle 1,2,5 ). Differences in patient groups, 12,13 and measurements of basal versus stress-provoked cortisol levels may also influence the results. 3,13 In general, the studies measured plasma cortisol levels 1Y3,5,6,9,11,13 or urinary free cortisol as measures of HPA axis activity.…”
mentioning
confidence: 80%
“…We previously reported an elevation in interdose blood cortisol levels after 3 weeks of chronic alprazolam treatment in the absence of any other evidence of drug withdrawal (Pomara et al 2004). In contrast, neither treatment with a low dose of alprazolam nor lorazepam resulted in a significant cortisol response.…”
Section: Introductionmentioning
confidence: 69%
“…The effects of these medications on plasma cortisol levels were also determined and described in a previous publication (Pomara et al 2004), which showed an interdose elevation in cortisol after 3 weeks of treatment with alprazolam 0.5 mg bid but not during treatment with lorazepam. In this report, we focused on possible sex-related differences in cortisol response in the subjects who were randomly assigned to receive 0.5 mg alprazolam or placebo who had cortisol levels available for the 3-week study (13 women and 12 men).…”
Section: Subjectsmentioning
confidence: 99%